SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL SCREENING OF SOME PYRAZOLES. - V. D. MANE; D. T. MAHAJAN; P. R. RAJPUT (International Journal of Pharma and Bio Sciences, 2015)
In the present study the pyrazole have been synthesized by the reaction of chalcone dibromide with phenyl hydrazine hydrochloride to afford the yellow solids of pyrazoles. The synthesized compounds have been confirmed by their chemical, analytical and spectral study and these synthesized compounds have been screened for their antimicrobial activity against some kharip plant pathogens viz Xanthomonas Campestris, Alternari Macrospora, Fusarium Spp.Pseudomonas syringae.